Pre-symptomatically detected novel variant of CPT1A deficiency: a case report - Ramachandran, Hari Prasath; U., Ramkumaar (International Journal of Contemporary Pediatrics, 2022)
CPT1A enzyme deficiency is a rare metabolic disorder of mitochondrial fatty acid oxidation, with late manifestations during infancy or childhood, including hypoketotic hypoglycemia and hepatic encephalopathy. Newborn screening in several countries include pre-symptomatic detection of CPT1A deficiency, which helps in early diagnosis and better management of the disorder. We report here a case of CPT1A deficiency, detected pre-symptomatically with newborn screening, which was confirmed by exome sequencing to be a novel c. 232G>A variant in exon 3 of CPT1A gene. This is a rare variant of uncertain significance which has not been reported in literature.